Toondoo comic in teaching speaking (a pre-experiment research) - Laila Wati; Siti Maysuroh; Sri Wahyuni; Ahmad Yusri; Nurul Hindri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
This research aims at finding the effectiveness of Toondoo Comic in teaching speaking at the second semester of Sendratasik Study Program of Hamzanwadi University in the academic year 2018-2019. This research was a pre experiment by using single group pre-test and post-test design. The population of the study was 47 students from A and B classes. The sample of the study was 17 students from class A. It was taken through purposive random sampling. A speaking test was used in collecting the data. The data collected were analyzed by using descriptive statistic, and paired sample t-test was used to test the hypothesis. It was performed using SPSS 22 for Windows. The result shows that the mean in the pre-test was 41.06 and was 60.71 in the post- test. Additionally, the hypothesis testing using paired sample t-test resulted significance (2-tailed) value level .000; it was lower than .05. This indicated that Toondoo comic was significantly effective in teaching speaking. Thus it is suggested that Tondoo comic is considered an alternative media in teaching and learning process.